Análise do impacto do treinamento aeróbico de resistência versus anaeróbico de força na fisiologia e morfologia cardíaca de atletas de alto rendimento através da ecocardiografia com speckle tracking - Pedro, Regis Luz (2022)
The various sports modalities determine different patterns of cardiac remodeling. Twodimensional echocardiography is the most widely used imaging method to assess exercise-related anatomical and functional adaptations in various sports modalities. However, the accuracy of traditional echocardiographic indices used for the assessment of myocardial function can be impacted by different factors, such as preand afterload to the ventricles, left ventricular (LV) geometry, and high interobserver variability. Echocardiography with speckle tracking is a technology recently incorporated into clinical practice that has advantages over traditional echocardiographic indices and has demonstrated greater accuracy in early detecting myocardial function changes in several cardiovascular diseases. However, its utility in the diagnosis and follow-up of functional alterations of the cardiac muscle in athletes is not yet well established. We conducted a descriptive cross-sectional study with the aim of comparing the findings of two-dimensional speckle tracking echocardiography between strength athletes and endurance athletes. A complete two-dimensional echocardiogram was performed, including the determination of the global longitudinal strain of the left ventricle (LV GLS) and right ventricle (RV GLS) by speckle tracking. Data are described as mean±SD or median and interquartile range. To compare the means between the two groups we used the unpaired t-test for variables with normal distribution and, alternatively, the Mann-Whitney test for variables with nonparametric distribution. We assessed the ability of a model composed of multiple independent variables to predict the categorical dependent variable by logistic regression. Data were analyzed using MedCalc for Windows statistical software (MedCalc Software, Ostend, Belgium, version 20.0), with the statistical significance threshold set at 0.05. The sample was composed of thirty-seven male athletes, 20 marathon runners and 17 strength athletes. The mean age was 37±8 years in the endurance group and 34±12 years in the strength group (p=NS), respectively. The strength group athletes had greater weight [91.4 (86 to 103) vs. 71.4 (65 to 75) kg, p<0.0001], greater body surface area [2.09 (2.0 to 2.2) vs. 1.85 (1.7 to 1.9) m2, p<0.001], higher body mass index [30.1 (26.7 to 32.1) vs. 22.8 (22.1 to 24.2), p<0.001] and higher resting heart rate [72 (66 to 82) vs. 59 (53 to 67) bpm, p<0.001] than marathon runners. Left ventricular mass was greater in the strength group [196.2 (160 to 213) vs. 167.9 (147 to 163) g, p=0.018], but with body surface area-adjusted mass index [90.4 (74 to 102) vs. 87.0 (81 to 99) g/m2, p=NS] and relative left ventricular wall thickness (RWT) [0.37 (0.34 to 0.39) vs. 0.33 (0.32 to 0.39), p=NS] showing no statistically significant differences between groups. Endurance athletes had higher indexed left atrial volumes [34.3 (30 to 43) vs. 29.5 (23 to 31) mL/m2, p=0.003] and right atrial volumes [26.9 (21 to 37) vs. 21.3 (18 to 25) mL/m2, p=0.005], larger baseline right ventricular diameter [39.7 (38 to 43) vs. 37.7 (35 to 40) mm, p=0.023] and higher left ventricular ejection fraction (LVEF) by Simpson method [61.4 (57 to 67) vs. 56.8 (53 to 62)%, p=0.021]. Analysis of LV diastolic function showed no significant differences between the groups. Both RV GLS [19.7 (17 to 22) vs 17.6 (15 to 18)%, p=0.035] and LV GLS [18.4 (17 to 19) vs 16.8 (15 to 17)%, p=0.001] were significantly higher in endurance athletes. Using a multivariate model, LV GLS, LV mass, and indexed LA volume were independent variables associated with the phenotype (strength=1 or endurance=0). The predictive model with these 3 variables had an AUC = 0.94 (95% CI 0.82 to 0.99, p<0.001)). LV GLS was associated with the phenotype even when corrected for age and LVEF [OR=0.48 (0.28- 0.81), p=0.006]. We conclude that athletes present cardiac morphological adaptations directly related to the training modality performed. In our study, LV GLS was an independent variable and statistically significant even when corrected for age and LVEF, suggesting its use in the echocardiographic evaluation of high performance athletes. Lower LV GLS values found for endurance athletes require further studies to identify which factors, in addition to training, contribute to this finding.